Effect of Alumina Contents on the Physicomechanical Properties of Alumina (Al2O3) Reinforced Polyester Composites - Fahamsyah H. Latief; Achmad Chafidz; Harri Junaedi; Adel Alfozan; Rawaiz Khan (Advances in Polymer Technology)
Polyester-based composites filled with various contents of alumina (Al2O3) (i.e., 0, 1, 5, and 10 vol%) have been fabricated in this study. Physical and mechanical properties of the composites have also been analysed. The analysis results showed that the experimental density of the polyester/alumina composites was smaller than the theoretical density, which could be attributed to the formation of voids during preparation of the composites. Meanwhile, the tensile strength, stiffness, and hardness of the composites increased with increasing alumina content, while the strain-at-break of the composites decreased. It was observed that the composites containing 5 vol% of alumina had the best tensile strength, stiffness, and hardness. The uniform distribution and dispersion of alumina particles were likely responsible for the improvement of the mechanical properties. In other hand, small decrease in tensile strength, stiffness, and hardness of composite was found in the composites with 10 vol% of alumina. The formation of agglomerates and voids was believed to be the main factor for the decrease of the both properties.